Application of hybrid analytical hierarchy process and complex proportional assessment approach for optimal design of brake friction materials. Issue 4 (1st May 2018) - Singh, Tej; Patnaik, Amar; Fekete, Gusztáv; Chauhan, Ranchan; Gangil, Brijesh
Abstract : In this article, hybrid analytical hierarchy process (AHP) and complex proportional assessment (COPRAS) approach was proposed to optimize automotive brake friction materials. Sixteen formulations based on phenolic resin, barium sulfate, Kevlar fiber, Lapinus fiber, multiwall carbon nanotube (MWCNT), nanoclay and graphite were formulated and evaluated for tribological properties. The tribo‐evaluation parameters such as coefficient of friction, friction‐fluctuations, friction‐variability, friction‐fade, wear, friction‐recovery, friction‐stability and disc temperature rise were considered as criterion for the performance optimization. The optimization of formulations was carry out in two steps: (1) finding the weight of each criterion by AHP method and (2) ranking the formulations with COPRAS method. The AHP‐COPRAS results show that the formulation of 50 wt% barium sulfate, 15 wt% phenolic resin, 2.5 wt% graphite, 5 wt% Kevlar fiber, 25 wt% Lapinus fiber with 2.5 wt% MWCNT exhibits the optimal tribological properties. POLYM. COMPOS., 40:1602–1608, 2019. © 2018 Society of Plastics Engineers